The Influence of Audit Quality, Good Corporate Governance, and Operational Efficiency on Company Profitability: - Suharna, Suharna; Syamsuri, Syamsuri (Indonesian Financial Review, 2025)
Transportation infrastructure companies operate in capital-intensive and highly regulated environments that demand strong internal controls and operational efficiency to maintain profitability. This study investigates the effects of audit quality, good corporate governance (GCG), and operational efficiency on profitability using secondary data from ten transportation infrastructure firms listed on the Indonesia Stock Exchange during 2020–2024. Multiple linear regression analysis reveals that operational efficiency significantly influences profitability, while audit quality and GCG show no significant partial effects. Nevertheless, simultaneous testing confirms that all variables jointly affect profitability. These findings indicate that profitability is primarily efficiency-driven, with governance and audit mechanisms serving complementary roles in enhancing stability and risk control rather than short-term financial performance.